Practical controls : a guide to mechanical systems - Calabrese, Steven R., 1965- (Fairmont Press ; Marcel Dekker, 2003)
Geared toward the HVAC professional, Practical Controls: A Guide to Mechanical Systems provides a solid foundation and well-rounded understanding of the role of controls in mechanical systems design and installation. This book takes a concise look at HVAC.
Includes index.
Keywords: Automatic control.; elektronické knihy; electronic books